2009
DOI: 10.1055/s-0029-1210817
|View full text |Cite
|
Sign up to set email alerts
|

Complement Component 3 (C 3) and Diabetes Mellitus

Abstract: Complement factor 3 (C3) phenotype and allele frequencies were defined in 312 patients with Type 1 diabetes (IDDM), 256 patients with Type 2 diabetes mellitus (NIDDM), 114 apparently healthy first-degree relatives of Type 1 diabetics, in 10 families (29 members) with a familial history of Type 1 or Type 2 diabetes, and 512 controls (blood donors). All persons investigated were Europeans. There is no evidence to suggest that genes linked to C3 influence susceptibility to Type 1 and Type 2 diabetes and to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Complement C3 and C4 are the major plasma proteins of the immune system complement pathways. The synthesis of serum complement protein C3 increased in response to inflammation and metabolic disorders, diabetes C3 levels elevated in T1DM Table 3 [ 60,61]. Zhain et al [62] reported that serum C3 and C4 of T1DM patients is significantly lower than corresponding value of healthy subjects and the lowest value of C3 was observed in patients with HbA1c >11%.…”
Section: Metabolic and Immune Parameters Relationship In Pediatricmentioning
confidence: 99%
“…Complement C3 and C4 are the major plasma proteins of the immune system complement pathways. The synthesis of serum complement protein C3 increased in response to inflammation and metabolic disorders, diabetes C3 levels elevated in T1DM Table 3 [ 60,61]. Zhain et al [62] reported that serum C3 and C4 of T1DM patients is significantly lower than corresponding value of healthy subjects and the lowest value of C3 was observed in patients with HbA1c >11%.…”
Section: Metabolic and Immune Parameters Relationship In Pediatricmentioning
confidence: 99%
“…Of these genes, C3 alleles and phenotypes have been evaluated in 312 individuals with type 1 diabetes, 114 healthy first-degree relatives, and 512 controls of European ancestry. 45 While there was no statistically significant evidence of association of C3 variants with type 1 diabetes risk, C3 levels in blood were highly elevated in recent-onset cases but only slightly elevated overall. More recently, the TEDDY study assessed 15 SNPs in the complement system in 5474 participants with follow-up that identified 413 with islet autoimmunity and 115 who developed type 1 diabetes.…”
Section: Complement Genes Outside Of the Mhc Regionmentioning
confidence: 83%
“…There are many other complement genes, including C1QC (complement C1q C chain, chr1p36.12), C5 (complement component 5, chr9q33.2), ITGAM (Integrin Subunit Alpha M, previously CD11B , CR3A , chr16p11.2), and C3 (Complement Component 3, chr19p13.3). Of these genes, C3 alleles and phenotypes have been evaluated in 312 individuals with type 1 diabetes, 114 healthy first‐degree relatives, and 512 controls of European ancestry 45 . While there was no statistically significant evidence of association of C3 variants with type 1 diabetes risk, C3 levels in blood were highly elevated in recent‐onset cases but only slightly elevated overall.…”
Section: Complement Genes Outside Of the Mhc Regionmentioning
confidence: 99%